2016
DOI: 10.1590/1807-3107bor-2016.vol30.0133
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the time-point of acid etching on the persistence of sealer residues after using different dental cleaning protocols

Abstract: Endodontic sealer residues remaining within the pulp chamber dentin after root canal obturation and cleaning with various solvents may compromise the appearance and the durability of dental restorations. Acid etching is routinely performed prior to application of dentine adhesive systems, but is effect on residual sealer material and the optimal time-point for performing etching, are unknown. Here, we evaluated the effect of acid etching on the dentin surface when performed either immediately or 7 days after r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
34
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(37 citation statements)
references
References 23 publications
1
34
1
1
Order By: Relevance
“…However, no differences were found in the ethanol groups, since ethanol is water‐miscible and the calcium silicate‐based sealer presents high solubility, regardless of the solvent polarity (Amoroso‐Silva, et al, ; Chávez‐Andrade, et al, ; Kuga, et al, ; Jordão‐Basso, Kuga, Bandéca, Duarte, & Guiotti, 2016). The results in the present study are differ from Jordão‐Basso, et al, () evaluation that observed a lower persistence of residues after xylol and acid etching carried out after 7 days. However, those authors evaluation was performed using epoxy resin‐based sealer.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…However, no differences were found in the ethanol groups, since ethanol is water‐miscible and the calcium silicate‐based sealer presents high solubility, regardless of the solvent polarity (Amoroso‐Silva, et al, ; Chávez‐Andrade, et al, ; Kuga, et al, ; Jordão‐Basso, Kuga, Bandéca, Duarte, & Guiotti, 2016). The results in the present study are differ from Jordão‐Basso, et al, () evaluation that observed a lower persistence of residues after xylol and acid etching carried out after 7 days. However, those authors evaluation was performed using epoxy resin‐based sealer.…”
Section: Discussioncontrasting
confidence: 99%
“…However, no differences were found in the ethanol groups, since ethanol is water-miscible and the calcium silicate-based sealer presents high solubility, regardless of the solvent polarity (Amoroso-Silva, et al, 2014;Ch avez-Andrade, et al, 2013;Kuga, et al, 2012a; Jordão-Basso, Kuga, Band eca, Duarte, & Guiotti, 2016). The results in the present study are differ from Jordão-Basso, et al, (2016) evaluation that observed a lower persistence of residues after xylol and Residues from the calcium silicate-based sealer negatively affected the extent of the hybrid layer formation in dentin. Ethanol solution and acid etching carried out after 7 days was the least affecting protocol to the hybrid layer formation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 1 2 ] Ethanol, xylol, amyl acetate, or eucalyptol have already been recommended for surface cleansing; however, their effectiveness is still questionable. [ 3 4 5 6 ] It favors the sealer residues persistence, which may cause discoloration of dental crown and/or negatively affect the adhesive interface between dentin and adhesive system, compromising the cosmetic restorations longevity. [ 1 2 3 4 5 6 7 8 ]…”
Section: Introductionmentioning
confidence: 99%
“…Ethanol is the most commonly used substance in cleaning protocol of dentin impregnated with endodontic sealer. [ 6 8 ] It is used alone or associated with diamond bur debridement in the cleansing treatment of dentin surface impregnated with zinc oxide-eugenol-based sealer (Endomethasone), reverting the bond strength of self-etching adhesive system to dentin. [ 8 ] On the other hand, ethanol is ineffective in cleansing dentin with epoxy-based sealer residue.…”
Section: Introductionmentioning
confidence: 99%